Integrasi Sustainable Development Goals dalam Kurikulum Merdeka: Tinjauan Literatur atas Peluang dan Tantangan Implementasi - Kandini, Gina Susi; Marselinda, Dyan; Rachman, Ichsan Fauzi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Education plays a crucial role in supporting the achievement of the Sustainable Development Goals (SDGs), particularly in providing inclusive and quality education. Indonesia's Kurikulum Merdeka, with its project-based and contextual learning approach, offers opportunities to integrate SDG values. However, its implementation still faces several challenges, such as infrastructure disparities, limited teacher competencies, and geographic and cultural obstacles. This study aims to examine the opportunities and challenges of SDG integration into Kurikulum Merdeka and to provide strategic recommendations for improving its effectiveness. The method used is a literature review with a descriptive-analytical approach, analyzing journal articles, policy documents, and relevant research reports. The findings indicate that although there is significant potential to develop a generation that is sensitive to global issues, several challenges must be addressed, including limited teacher understanding, unequal distribution of educational resources, and cultural barriers. To enhance SDG implementation, it is recommended to improve teacher competencies, provide learning materials tailored to local needs, and foster collaboration with surrounding communities. In addition, an effective monitoring system is essential to oversee and evaluate the progress of SDG implementation in education. The role of Teacher Education Institutions (LPTKs) is also vital in preparing educators capable of integrating SDG values into the teaching and learning process. This study is expected to offer guidance for policymakers and education practitioners in formulating more efficient strategies to achieve sustainable development goals.